Application of organic matter to enhance phytoremediation of mercury contaminated soils using local plant species: a case study on small-scale gold mining locations in Banyuwangi of East Java - N Muddarisna; B C Siahaan (Brawijaya University, 2014)
The discharge of small-scale gold mine tailing to agricultural lands at Pesanggaran village of Banyuwangi Regency caused soil degradation as indicated by reduced crop production. This soil degradation is mainly due to the toxicity of mercury contained in the tailing. The purpose of this study was to explore the potential of three local plant species, i.e. Lindernia crustacea, Digitaria radicosa, and Cyperus kyllingia for phytoremediation of agricultural land contaminated gold mine waste containing mercury, and its influence on the growth of maize. Six treatments (three plant species, and two levels of organic matter application) were arranged in a randomized block design with three replicates. Maize was grown on soil after phytoremediation for 8 weeks. The results showed that among the three plant species tested, Cyperus kyllingia was the potential candidate plant species for phytoremediation of soil contaminated with gold mine tailing containing mercury because of its ability to accumulate mercury from 32.06 to 73.90 mg / kg of soil in 60 days. Phytoremediation of mercury contaminated soil using Cyperus kyllingia using increased maize yield by 126% compared to that the biomass yield of maize grown on soil without phytoremediation. Induce phytoremediation needs to be carried out to accelerate the process of remediation of mercury contaminated soils.